Analysis of Vocational Students’ Problem-Solving Competencies in Resolving Case Studies in Statistics: Analysis of Vocational Students’ Problem-Solving Competencies - Fauzi, Ilham Saiful; Sutrisno, Sutrisno; Selviana, Vuvut; Bakhrudin, Bakhrudin (Journal of Vocational Education Studies, 2025)
The rapid advancement of technology presents significant challenges, particularly in vocational education, where the aim is to produce skilled graduates ready for the workforce. This study analyzes the problem-solving competencies of vocational students when resolving case studies in Statistics courses. A descriptive qualitative approach was employed, involving 90 students divided into 30 groups as subjects. Primary data were gathered from the students' case study analyses, which were classified and analyzed according to Polya’s problem-solving stages. Findings revealed that students demonstrated varying levels of initiative in understanding problems and developing solutions. Specifically, 20% of the groups fell into the substance category, 46,67% into result, and 33,33% into completion. Substance groups struggled with planning and data collection, while result groups exhibited minor errors in implementing their plans, particularly in data processing and presentation. Meanwhile, completion groups showed a comprehensive understanding and effective problem resolution. The analysis of these problem-solving capabilities provides a foundation for a deeper evaluation of instructional effectiveness and the development of targeted teaching strategies.